Effect of Mechanical Surface Treatment on the Tensile Bond Strength of Repaired Acrylic Denture Base Resin Cured by Two Different Techniques - Hummudi, israa (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To evaluate and compare the effect of mechanical surface treatment (groove, aluminum oxide particles)with 45 degree bevel type of joint on tensile bond strength of acrylic specimens repaired by two curing methods(microwave and water both).Methodology: Eighty specimens (80) were prepared from pink heat cure acrylic resin. They were divided into twomain groups (40 specimen repaired by microwave energy and 40 specimens repaired by water bath method).Eachgroup can be divided into four subgroups of ten according to the surface treatment. The control group A was leftintact, group B received no surface treatment, group C and D received surface treatment by (groove, 50 m aluminumoxide particles). Specimens were tasted by using an instron universal testing machine until fracture occurs.Result: The results indicate that nurses have adequate knowledge toward general information on infection, infectioncontrol strategy, causes, prevention, sterilization and disinfection, and healthy conditions in operating roomenvironment. Regarding practices, the results indicated inadequate practices concerning the standard precautionduring wearing operation clothing, patient's preparation, and hand washing practices. While, their practicesconcerning tools and equipment preparations were adequate. There is a significant relationship between nurses’knowledge and practices and their educational level and years of experience.Recommendation: It can be concluded that mechanical surface treatment prior to denture base repair resulted in asignificant improvement the tensile bond strength of denture base resin.